ESTIMASI NILAI MODULUS REAKSI TANAH DASAR (NILAI ‘k’) PADA MATERIAL TANAH LEMPUNG PENIRAMAN - Dian Sudiyono; Slamet Widodo; Eti Sulandari (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Subgrade is a very important factor in the field of civil engineering, especially in designing the pavement, both rigid and flexible pavements pavement. According to some studies of land in West Kalimantan, especially land Peniraman have clay soil conditions that have small pebbles. Clay is technically more advantageous because it has a carrying capacity is high enough so that in designing the pavement is excellent for use as road subgrade. This research was carried out without disturbing the original soil conditions are then carried out by testing the physical properties and mechanical properties of the soil. Testing the physical properties of soil carried out by three methods: USCS, AASHTO, and the USDA. Based on the method USCS unknown land peniraman classified as ML (silt inorganic, fine sand once, powdered rock, fine sand clayed or argillaceous) and according to AASHTO classified land clayed with general levels most basic soil moderate to poor, while according to the USDA soil classified as loam or Clay. As for testing the mechanical properties of soil compaction test done and compressive strength test soil by CBR test and the test load plate to get the subgrade modulus value or the value of "k". In addition to getting the CBR value and the value of "k", the results of this research will also get the relationship of the two values ​​which will then be displayed in graphic design NAASRA. Testing was conducted in the laboratory using existing CBR tool with 2 variations sample of soak and soak and variations in energy (collision) is given. Soaking were conducted for 4 days to get a critical CBR soil tested, while the energy variations that give the 10, 30, and 56 collision. The results showed it turns out that soaked CBR generate value and value "k" is far lower than the soil soaked, it is due to the development that occurs as a result of immersion for 4 days to obtain the critical value which is used to design a pavement. Similarly, land with energy 56 collisions produce CBR value and the value of "k" is higher than the ground with energy 10 and 30 collision, This is the land with energy 56 collisions have a density that is far better than the 10 and 30 collisions so that when pressure tests produce CBR value and the value of "k" is higher the closer the value of design. Keywords :        Soil Clays Peniraman, Maximum Dry Density (γdry), Optimum Water Content (Woptimum), CBR, value 'k' (k value).